Tecnología digital aplicada en la Odontología Forense para el reconocimiento de cadáveres. - Pacari Tiche, Sammia Mishel (2025)
The present research work aimed to describe the digital technologies for corpse recognition in Forensic Dentistry through a literature review. The PRISMA methodology was used, and 20 articles were found in the following databases: PubMed, Scielo, and Google Scholar. The main findings were digital radiographs, tomography, 3D printing, digital photography, intraoral scanning, image monitoring, and virtopsy. As a result, digital technologies benefit human identification, as they offer greater accuracy in capturing anatomical details. Furthermore, digitization streamlines forensic processes. It allows for comparing antemortem and postmortem data; most importantly, digital data can be stored in databases. On the other hand, these technologies present limitations in terms of cost and limited access in developing countries. There is no universal protocol to facilitate the work, and trained personnel are required to operate these devices. Finally, it is important to mention that forensic dentistry technologies have advanced spontaneously in developed countries, while in Ecuador, there is still no evidence that they have been fully implemented.